Study on Efficacy of Dexamethasone and Methylprednisolone in Postoperative Swelling and Trismus Following Mandibular 3rd Molar Surgery - Uzzaman, Md Helal; Rahman, AFM Shahidur; Rahman, Md Masudur; Alam, Md Shafiqul; Rahman, Mohammad Shameemur; Rubel, ATM Tarifuzzaman; Howlader, Liton Bhushan (Journal of Shaheed Suhrawardy Medical College, 2018)
Introduction: Surgical removal of 3rd molars causes significant swelling and trismus which are unpleasant and uncomfortable for the patient even when teeth are removed by gentle surgical technique. Our surgical procedures can lead to serious inflammatory reactions in the facial soft tissues and should be minimized as much as possible. The aim of this study was to compare the effect of a single intramuscular (I/M) dose of two different corticosteroids on postoperative facial soft tissue swelling and trismus. Methodology: This interventional study was conducted in oral and maxillofacial surgery department of BSMMU. 60 patients (33 male and 27 female)were included in this study and were randomly divided into two groups. In Group-I, 30 patients were included and 4mg of Dexamethasone was injected into the Deltoid region 30 minutes prior to extraction of mandibular 3rd molars. In Group-II,another 30 patients were included and 40mg of Methylprednisolone was injected into theDeltoid region 30 minutes prior to extraction of mandibular 3rd molars.Facial swelling was evaluated preoperatively, on 2nd POD and 7th POD by using measuring tape. Trismus was determined by measuring the maximum inter-incisal distance pre-operatively, on 2nd POD and 7th POD by vernier caliper. Result:Result showed that swelling and trismus was significantly reduced in both groups, p>0.05(not significant). Conclusion:The result concluded that the preoperative single dose of I/M administration of Dexamethasone or Methylprednisolone significantly reduces postoperative swelling and trismus after surgical removal of mandibular 3rd molars. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 60-64